2015
DOI: 10.14814/phy2.12345
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived circulating endothelial cells in peripheral blood of newborn infants with seizures: a potential biomarker for cerebrovascular injury

Abstract: Neonatal seizures have been associated with cerebrovascular endothelial injury and neurological disabilities. In a piglet model, the long-term loss of endothelial regulation of cerebral blood flow coincides with the surge of brain-derived circulating endothelial cells (BCECs) in blood. We hypothesized that BCECs could serve as a noninvasive biomarker of cerebrovascular injury in neonates with seizures. In a prospective pilot feasibility study, we enrolled newborn infants with confirmed diagnoses of perinatal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In newborn pigs of both sexes, epileptic seizures lead to cerebral vascular injury, apoptosis, and long-term insufficiencies in cerebral vascular functions, including sustained loss of endothelium- and astrocyte-mediated regulation of CBF ( 5 8 ). Clinical studies in newborn babies with epileptic seizures caused by neonatal hypoxic-ischemic encephalopathy and severe intraventricular hemorrhage (IVH III–IV) revealed the occurrence of cerebral vascular damage diagnosed by the surge of circulating endothelial cells of brain origin (BCECs) in peripheral blood ( 9 ). Cerebral vascular insufficiencies have been also detected in epileptic patients ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In newborn pigs of both sexes, epileptic seizures lead to cerebral vascular injury, apoptosis, and long-term insufficiencies in cerebral vascular functions, including sustained loss of endothelium- and astrocyte-mediated regulation of CBF ( 5 8 ). Clinical studies in newborn babies with epileptic seizures caused by neonatal hypoxic-ischemic encephalopathy and severe intraventricular hemorrhage (IVH III–IV) revealed the occurrence of cerebral vascular damage diagnosed by the surge of circulating endothelial cells of brain origin (BCECs) in peripheral blood ( 9 ). Cerebral vascular insufficiencies have been also detected in epileptic patients ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…intraventricular hemorrhage (III/IV); these infants also had poor neurological outcome (39). Overall, our experimental and clinical findings suggest that BCEC levels in peripheral blood offer a proper biological indicator that reflects cerebrovascular insult and recovery.…”
Section: Discussionmentioning
confidence: 71%
“…The presence of BCECs serves as an early systemic indicator of the severity of the endothelial damage that predicts the later occurrence of cerebral vascular dysfunction (35). Importantly, our pilot clinical studies in newborn babies with seizures of different etiologies suggest that the number of BCECs in peripheral blood can serve as an early predictor of adverse neurological outcome (39).…”
mentioning
confidence: 89%
“…Neurovascular unit disruption has been demonstrated in neonates with HIE and animal models of HI. Direct injury to neurovascular endothelial cells that can last between days to weeks has been demonstrated in human neonates with HIE (Pourcyrous et al 2015). Pourcyrous and colleagues demonstrated that newborns with HIE had significantly greater brain-derived endothelial cells in circulating blood which implies damage to the cerebral vasculature.…”
Section: Blood-brain Barrier Disruption Following Perinatal Brain Injuriesmentioning
confidence: 99%
“…However, very little is known regarding the role BBB-disruption plays in the evolution of neonatal seizure. To the best of my knowledge, the only pieces of evidence that BBB-disruption following HIE are associated with seizures are from Pourcyrous et al, 2015and Schiering et al, 2005. Pourcyrous and colleagues (2015 found that neonates with seizures following HIE have been found to have increased levels of circulating brain-derived endothelial cells than control babies and HIE babies without seizure, which suggests that seizures are associated with damage to the NVU which is essential for BBB integrity.…”
Section: Blood Brain Barrier Disruption and Neonatal Seizuresmentioning
confidence: 99%